ISLAMIC CENTRE DI ACEH SELATAN (INTANGIBLE METAPHOR) - Mitra Ariansyah; Muhammad Joni (Rumoh Journal of Architecture, 2021)
South Aceh is included as an area that has a high Islamic value, almost in every village has a mosque and almost inevery village / kelurahan there is a Taklim Council and Islamic Boarding School, for now the number of boarding schoolin South Aceh Regency there are Sixty-five Islamic boarding schools and two mosques. hundred and seventy mosques.Therefore, it is necessary to have a center for Muslim activities in South Aceh. The Islamic Center in South Aceh islocated in the City of Fajar, North Kluet District, the purpose of this building is to provide services to the community,empower and improve religious institutions, increase knowledge and faith, aiming at realizing a central container for thedevelopment of Islamic activities in South Aceh that can support activities in the fields of da'wah, social education, andculture. The district-level Islamic Center is the Islamic Center which is located in the district's local area and has a district level mosque, namely the grand mosque, which is equipped with facilities such as worship/worship, mu'amalah facilitiesand tarbiyah facilities. more oriented to the operational development of da'wah directly. The application of the Intangible Metaphor theme in the Islamic Center building transforms from the shape of the hand when praying to forming 10 building blocks according to the number of fingers. The theme of the Intangible Metaphor is expected that according to its function, this building itself can be a media provider and information about the Islamic Center of South Aceh. Land area of 40,000m², ground floor area of 9,505m², overall floor area of 38,020 m², single mass, with a capacity inside the building to accommodate 3000 worshipers, and outside the building to accommodate 1000 worshipers. The main activity facilities are Prayer Room, Management Office, Baziz Office, Classroom, Library, Mess and Radio Da'wah. While the support is an auditorium, restaurant and guard post.